Morbidity and mortality weekly report, Vol. 6, no. 29, For release July 26, 1957 - United States Dept. of Health, Education, and Welfare Public Health Service; United States National Office of Vital Statistics
Provisional information on selected notifiable diseases in the United States and on deaths in selected cities for week ended July 20, 1957 -- Number of deaths in 114 selected cities -- Quarantine measures, Immunization information for international travel Epidemiological reports: Influenza -- Encephalitis -- Rabies in animals -- Sore throat, etiology unknown -- Chemical poisoning -- Gastro-enteritis Table 1. Cases of specified notifiable diseases: continental United States -- Table 2. Cases of specified notifiable diseases: United States, each division and state, Alaska, Hawaii, and Puerto Rico for weeks ended July 21, 1956 and July 20, 1957 -- Table 3. Deaths in selected cities by geographic division -- Table 4. Deaths in selected cities